Development of Media with Pictures for Kindergarteners’ Reading Readiness - Rita Kurnia; Hukmi Hukmi; Defni Satria (AL-ISHLAH: Jurnal Pendidikan, 2022)
This is a developmental study that began with observations of some early childhood children in Siak Sri Indrapura, Indonesia, who lacked reading readiness. Seeing the potential of Malay folklore, a learning media for Malay folklore pictorial stories was developed. The process of creating media begins with the determination of the story and theme, followed by the creation of designs and product models. Validator assessment is feasible and may be used to determine a child's readiness for reading. To determine the effectiveness of the media, this study used a quantitative method with a two-group post-test design. According to the t-test results, a t-observed value of -8,175 with a significance value of 0.000 indicated that there was a difference in reading readiness between the experimental and control groups, indicating that the Malay folklore pictorial story media was effective for early childhood reading readiness in Siak Sri Indrapura.